2009
DOI: 10.1007/s00239-009-9283-9
|View full text |Cite
|
Sign up to set email alerts
|

Distinct Evolutionary Patterns Between Two Duplicated Color Vision Genes Within Cyprinid Fishes

Abstract: We investigated the molecular evolution of duplicated color vision genes (LWS-1 and SWS2) within cyprinid fish, focusing on the most cavefish-rich genusSinocyclocheilus. Maximum likelihood-based codon substitution approaches were used to analyze the evolution of vision genes. We found that the duplicated color vision genes had unequal evolutionary rates, which may lead to a related function divergence. Divergence of LWS-1 was strongly influenced by positive selection causing an accelerated rate of substitution… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
8
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 65 publications
0
8
0
Order By: Relevance
“…We note that our study is the first, to our knowledge, to explicitly investigate divergence among both orthologs and paralogs in the same data set. Finally, it is noteworthy that several studies have used the results of Clade model analyses to support arguments of positive selection [101,102], but whether or not the relevant ω estimates significantly exceed ω = 1 has not been explicitly tested, as we have done here; this point, while at first glance technical in nature, is of large importance, as ω estimates larger than ω = 1 may occur due to chance.…”
Section: Discussionmentioning
confidence: 90%
“…We note that our study is the first, to our knowledge, to explicitly investigate divergence among both orthologs and paralogs in the same data set. Finally, it is noteworthy that several studies have used the results of Clade model analyses to support arguments of positive selection [101,102], but whether or not the relevant ω estimates significantly exceed ω = 1 has not been explicitly tested, as we have done here; this point, while at first glance technical in nature, is of large importance, as ω estimates larger than ω = 1 may occur due to chance.…”
Section: Discussionmentioning
confidence: 90%
“…Li et al, 2011 Feline cauxins (urinary proteins) Orthologs CmC, CmD Liao et al, 2010 Rhododendron small heat shock proteins Paralogs CmD Liu et al, 2010 Mammalian prestins (auditory motor proteins) Orthologs CmC Wang et al, 2010 Vertebrate plasma membrane transport proteins Paralogs CmC Wei et al, 2010 Feline major-histocompatibility complex peptide binding regions Paralogs CmC Hughes et al, 2009b Mammalian UCP mitochondrial anion carriers Paralogs CmC Hughes et al, 2009a Primate melanocortin receptors Orthologs CmC Li et al, 2009 Cyprinid cone opsins (visual pigment proteins) Paralogs CmC Mondragon-Palomino et al, 2009 Orchid class-B MADS-box transcription factors Paralogs CmC, CmD Zhao et al, 2009 Mammalian rod opsins (visual pigment proteins) Orthologs CmC Des Marais and Rausher, 2008 Morning glory acanthocyanin pigment pathway reductases Paralogs CmC Haudry et al 2008 A variety of gene fragments from selfing and non-selfing grasses Orthologs CmC Summers and Zhu, 2008 Cichlid prolactin hormones Paralogs CmD Alverson, 2007 Diatom silicon transporters Orthologs CmD Hernandez-Hernandez et al, 2007 Eudicot class-B MADS-box transcription factors Paralogs CmD Li et al, 2007 Bat FoxP2 transcription factors Orthologs CmC Balakirev et al, 2006 Drosophila β-esterase enzymes Paralogs CmD Bielawski and Yang, 2004 Primate RNases and globins Paralogs CmD goodness-of-fit of CmC (Weadick and Chang, in press). Briefly, CmC and its typically used null model, M1a, differ not just in whether˘is heterogeneous between among clades, but also in how they model among-site˘variation.…”
Section: Model(s) Usedmentioning
confidence: 99%
“…Studies demonstrating that regressive evolution of eyes in subterranean organisms is associated with loss of gene function at the molecular level are limited to subterranean diving beetles (Leys et al 2005), Mexican cavefish (Yokoyama et al 1995), marsupial moles (Springer et al 1997), naked mole rats (Kim et al 2011), and cave-roosting bats (Zhao et al 2009a). Several additional studies found no support for LOF of vision-related genes in a variety of subterranean organisms (Yokoyama and Yokoyama 1990a,b;Crandall and Hillis 1997;Janssen et al 2000;Smulders et al 2002;Jeffery 2005Jeffery , 2009Li and He 2009;Li et al 2009b).…”
mentioning
confidence: 99%